Synthesis and structural characterization of 6-(N-Methyl-pyridin-2-ylcarbamoyl)-pyridine-2-carboxylic acid methyl ester isomers - Maisara Abdul Kadir,; Nafisah Mansor,; Uwaisulqarni Md. Osman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
A series of monoamide isomers have been successfully synthesised and characterised using combination of common spectroscopic techniques such Fourier Transform Infrared (FT-IR), 1H and 13C Nuclear Magnetic Resonance (NMR) and Ultraviolet-visible (UV-vis). The monoamide compounds namely 6-(3-methyl-pyridin-2-ylcarbamoyl)-pyridine-2-carboxylic acid methyl ester (L1), 6-(4-methyl-pyridin-2-ylcarbamoyl)-pyridine-2-carboxylic acid methyl ester (L2), 6-(5-methyl-pyridin-2-ylcarbamoyl)-pyridine-2-carboxylic acid methyl ester (L3) and 6-(6-methyl-pyridin-2-ylcarbamoyl)-pyridine-2-carboxylic acid methyl ester (L4) were prepared from reaction between 6-(methoxycarbonyl)pyridine-2-carboxylic acid with 2-amino-N-methylpyridine (where N = 3, 4, 5 and 6) by using acyl chloride reaction. In this present studies, the synthesis and characterization of these compounds are discussed along with the inductive effects contributed by methyl substituted groups at the pyridine ring.